Prenatal exposure to ambient PM2.5 and its chemical constituents and child intelligence quotient at 6 years of age - Xiaowei Sun; Cong Liu; Honglei Ji; Weihua Li; Maohua Miao; Wei Yuan; Zhengwei Yuan; Hong Liang; Haidong Kan (Ecotoxicology and Environmental Safety, 2023)
There are limited studies on the associations between prenatal exposure to constituents of fine particulate matter (PM2.5) and children’s intelligence quotient (IQ). Our study aimed to explore the associations between prenatal PM2.5 and its six constituents and the IQ levels of 6-year-old children. We included 512 mother-child pairs. We used a satellite-based modelling framework to estimate prenatal PM2.5 and its six constituents (ammonium, sulfate, nitrate, organic carbon, soil dust, and black carbon). We assessed the children’s IQ using the short form of the Wechsler Intelligence Scale. Perceptual Reasoning Index (PRI), Verbal Comprehension Index (VCI), and Full Scale IQ (FSIQ) scores were computed. The multiple informant model (MIM) was applied to explore the trimester specific effects of PM2.5 and its six constituents’ exposure on children’s PRI, VCI, and FSIQ. To examine whether the duration of breastfeeding and physical activity (PA) could modify the effects of PM2.5 on children’s IQ, we stratified the analyses according to the duration of breastfeeding (≤6 and >6 months) and time of outdoor activities after school (≤2 and >2 h/week). The first trimester PM2.5 and its five constituents’ exposures were inversely associated with FSIQ [β = −1.34, 95 % confidence interval [CI] (−2.71, 0.04) for PM2.5] and PRI [β = −2.18, 95 %CI (−3.80, −0.57) for PM2.5] in children. The associations were magnified among boys and those with less outdoor activities or shorter breastfeeding duration. Our results indicate that prenatal PM2.5 and several of its main constituents’ exposure may disrupt cognitive development in children aged 6 years. More PA and longer breastfeeding duration may alleviate the detrimental effects of prenatal PM2.5 exposure on children’s cognitive function.